The Etiologic Profile of the Pediatric Seizure: An Epidemiological Study from Iran - Taherian, Reza; Feshangchi-Bonab, Mohammad; Rezayi, Alireza; Jahandideh, Mahdieh (International Clinical Neuroscience Journal, 2017)
Background: Seizures are one of the most common neurologic disorders in children. The aim of this study is to determine the main etiologies of seizure in children. Methods: Children with a complaint of seizure in Loghman Hakim hospital, from June 2014 to January 2016 were evaluated. The final diagnosis of seizure was made by a pediatric neurologist. The age, sex, type of seizure, associated fever, history of head trauma and other variables related to seizure in pediatric group were reviewed from the medical records. Results: A total of 200 children with a diagnosis of seizures were included in this study. A total of 59% were male patients. The age of the patients ranged from 3 months to 102 months with a mean of 23 months.About one-quarter of the patients had focal seizures while others had generalized seizures. Sixteen patients (8%) had a positive family history of epilepsy. Of total 126 patients (63%) experienced their first lifetime seizure. The body temperature of the patients ranged from 36.1 °C to 39.8 °C with a mean of 38.2 °C. The etiologies of seizures were febrile seizure (82%), vaccine-associated seizures (3%), hypoglycemia (6%), hypocalcemia (2%), hyponatremia (2%), encephalopathy (2%), hyperglycemia (1%), epilepsy (1%) and intracerebral hemorrhage (1%). Conclusion: While fever is the most common etiology of seizure in children, hypoglycemia should be taken into consideration as the second most common etiology of seizure. Although other etiologies such as hyponatremia and intracerebral hemorrhage are less common, they should be kept in mind due to their life-threatening complications. Hence, the results of this study underscores the importance of history and laboratory findings of the children with seizure.